The BEACH Protein LRBA Promotes the Localization of the Heterotrimeric G-protein G(olf) to Olfactory Cilia - Kurtenbach, Stefan (Sci Rep, 2017)
BEACH domain proteins are involved in membrane protein traffic and human diseases, but their molecular mechanisms are not understood. The BEACH protein LRBA has been implicated in immune response and cell proliferation, and human LRBA mutations cause severe immune deficiency. Here, we report a first functional and molecular phenotype outside the immune system of LRBA-knockout mice: compromised olfaction, manifesting in reduced electro-olfactogram response amplitude, impaired food-finding efficiency, and smaller olfactory bulbs. LRBA is prominently expressed in olfactory and vomeronasal chemosensory neurons of wild-type mice. Olfactory impairment in the LRBA-KO is explained by markedly reduced concentrations (20–40% of wild-type levels) of all three subunits α(olf), β(1) and γ(13) of the olfactory heterotrimeric G-protein, G(olf), in the sensory cilia of olfactory neurons. In contrast, cilia morphology and the concentrations of many other proteins of olfactory cilia are not or only slightly affected. LRBA is also highly expressed in photoreceptor cells, another cell type with a specialized sensory cilium and heterotrimeric G-protein-based signalling; however, visual function appeared unimpaired by the LRBA-KO. To our knowledge, this is the first observation that a BEACH protein is required for the efficient subcellular localization of a lipid-anchored protein, and of a ciliary protein.